THE EFFECT OF HEATING ON THE SURFACE AREA, POROSITY AND SURFACE ACIDITY OF A BENTONITE - Noyan H.; Önal M.; Sarikaya Y. (My University, 2006)
The Hançili bentonite from Turkey shows significant changes in surface area, micro- and mesoporosity, surface acidity and acid strength with heating from 100 to 900°C for 2 h. The specific surface area (S) and specific micro-mesopore volume (V) of the original and heated samples were evaluated from N2 adsorption and desorption data, respectively, by standard methods. The adsorption of n-butylamine from the solution in cyclohexane on the samples was used to determine the total surface acidity (nm) and the adsorption equilibrium constant (K) was taken as a measure of the acid strength. S, V and nm having initial values of 98 m2g-1, 0.080 cm3g-1 and 4.8 × 10-4 mol g-1, respectively, stayed approximately constant as the temperature increased to 450°C and then decreased almost in parallel with each other, reaching their minimum or zero at 900°C. The total surface acidity, in general, declines with increasing temperature. The most acidic sites, however, increase with heating, and especially at dehydration and dehydroxylation. Acid strength reaches its maximum during the dehydroxylation phase at ~600°C. It was concluded that the total surface acidity does not necessarily parallel the strength of the most acid sites. Copyright © 2006, The Clay Minerals Society.
Keywords: ACID STRENGTH; BENTONITE; HEATING; SURFACE ACIDITY; SURFACE AREA